Evolução microestrutural de soldas produzidas com a mistura das ligas AWS ERNiCrMo-3 e AWS ERNiCrMo-4 submetidas a tratamentos térmicos de envelhecimento - Santiago, Kamilla Giló (2018)
Tandem GMAW process with isolated potential configuration has been used to expand the horizon of this process, allowing the alloying in-situ development by welding with deposition of different materials in different proportions. From this feature, thicker coatings were carried out by T-GMAW with simultaneous deposition of AWS ERNiCrMo-3 (Inconel 625) and AWS ERNiCrMo-4 (Hastelloy C276) nickel-based alloys in order to obtain alloys manufacture in-situ with distinct chemical compositions which, in turn, could have mechanical strength properties and corrosion performance. The welds were performed with the use of out-of-phase current pulse, the electrodes positioned one behind the other, where the wire with the highest feed speed came forward. This step provided the in-situ manufacture of three kinds of alloys named Alloys in-situ A, B and C, with the proportions of 50% AWS ERNiCrMo-3 plus 50% AWS ERNiCrMo- 4, 35% AWS ERNiCrMo-3 plus 65% AWS ERNiCrMo-4 and 65% AWS ERNiCrMo-3 plus 35% AWS ERNiCrMo-4. In sequence, these in-situ alloys were aged under two temperature conditions: 650°C and 950°C for 10h, 50h, 100h and 200h. The microstructural characterization was performed using light microscopy (LM), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray energy dispersive spectroscopy (EDS). The impact toughness and hardness of the alloys in-situ were evaluated according to ASTM E23 standards (Charpy V-notched impact tests) and ASTM E384 (Vickers microhardness). The corrosion resistance was evaluated by immersion test according to ASTM G48. The microstructure of the alloys manufacture in-situ consisted of a γ-fcc matrix with secondary phases rich in Mo, W and Nb. In addition, complex structures constituted by core of (TiNb)N and a shell of NbC were also found. After aging at 650°C the precipitation of γ" phase was found into the γ-fcc matrix, displaying different intensities according the kind of in-situ alloy. In addition, precipitation along grain boundaries were observed. TEM results shown that in in-situ alloy A a Mo-rich M 23 C 6 carbide particle was identified at the grain boundary. Concerning the aging at 950°C, the in-situ alloy B stood out due to the high intensity of precipitation of larger secondary phases at the grain boundaries, in contrast with the in- situ alloy C that showed a thin and discrete precipitation. In general, the microhardness of the alloys increased with the aging time to 650°C due to the γ" phase. Alloys in-situ A and C showed greater impact toughness and resistance to corrosion than alloy B, even after aging.